Fistula Recurrence: A Clinical Reality after Successful Endoscopic Closure of Laparoscopic Sleeve Gastrectomy Fistulas - Patricia Sousa; Carlos Noronha Ferreira; João Coutinho; Fátima Carepa; Rosário Rosa; Andreia Barão; Carlos Marques Ferreira; José Girao; António Ruivo; Henrique Bicha Castelo; João Lopes; Amélia Almeida; et al. (GE: Portuguese Journal of Gastroenterology, 2018)
Background and Aims: Laparoscopic sleeve gastrectomy (LSG)-related fistulas are important and potentially fatal complications. We aimed at determining the incidence, predictive factors, and management of recurrence of post-LSG fistulas. Methods: This is a retrospective cohort study of 12 consecutive patients with LSG fistulas managed endoscopically between 2008 and 2013. We analyzed factors associated with recurrence of post-LSG fistulas and the efficacy of a primarily endoscopic approach to manage fistula recurrence. Results: The average age at fistula detection after LSG was 43.3 ± 10.9 years, and 10 (83%) patients were female. The median interval between surgery and initial fistula detection was 14 (4–145) days. Fistulas were located at the gastric cardia in 9/12 patients. A median of 4 (1–10) endoscopies were performed per patient until all fistulas were successfully closed. The median follow-up was 30.5 (15–72) months. Fistula recurrence was detected in 3 (25%) female patients with an average age of 31.7 ± 7.9 years after a median of 119 (50–205) days of the initial fistula closure. Fistulas in all 3 patients recurred at the gastric cardia and were successfully managed endoscopically. There was a second recurrence in 1 patient after 6 months, and she was re-operated with anastomosis of a jejunal loop at the site of the fistula orifice at the gastric cardia. We did not find any factors at initial fistula detection that were significantly associated with fistula recurrence. There were no deaths related to initial fistula after LSG and fistula recurrence. Conclusions: A primarily endoscopic approach is an effective and safe method for the management of fistulas after LSG. Fistula recurrence occurred in 25% of patients and was managed endoscopically. Key Messages: Although we could not define predictive factors of post-LSG fistula recurrence, it is a clinical reality and can be managed endoscopically.